Revamping real estate document storage with blockchain. (7th January 2021) - Anandan, Arshida K.; Dighe, Pratik M.; Gaikwad, Ajay D.; Chavan, Pallavi; Chavan, Madhuri
This paper reports the usage of blockchain technology in today's asset trade. Blockchain analyses disruptive power towards real estate. The real estate sector's problem is that there are various ways in which high-profile people exploit the authentic user by taking of their land and manipulating the documents. The paper-based documentation linked with real estate is more vulnerable to forgery than digital documents. This paper describes how blockchain is applied to the real-estate sector. The blockchain aims to maintain the history of all real estate transactions and registration in a network using smart contracts. Blockchain allows each property, anywhere, to have a digital address for the ownership and other attributes to maintain all past transactions. Blockchain speeds up the transactions from days/weeks/months to minutes/seconds, which has huge impact on society. This paper describes the solution to ensure the use of blockchain in land records.